"Tourism for all?" Considering social tourism: a perspective paper. Issue 1 (19th December 2019) - McCabe, Scott
Abstract : Purpose: This paper aims to outline the context for social tourism as an approach that can help deliver societal goals, such as reducing inequalities, as well as benefits for deserving beneficiaries and the tourism industry. The paper highlights how social tourism can develop in the future. Design/methodology/approach: The paper takes a conceptual approach to discuss these issues. Findings: This paper finds that there is a great deal of potential for social tourism to contribute to the future sustainability in the tourism industry. Originality/value: This paper provides a concise overview of the topic of social tourism and a model that can help researchers and other readers to understand the ways that social tourism can contribute towards a more sustainable and equitable tourism future.